(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
Coupling reaction between aryl halide and terminal alkyne in Sonogashira coupling reaction is important due to its extensive application in the resynthesis of natural products, production of drugs, dyes, and polymers. Efforts to increase rate of reaction has involved exploration of new catalysts. The current catalysts such as phosphine-based complexes are costly, air-sensitive and environmentally harmful. Nickel(II) Schiff base complexes were synthesized by reacting aromatic Schiff base ligands 2,2'-((1E,1'E)-(1,2-phenylenebis(azanylylidene))bis(metha-nylylidene))diphenol (L1H), 2,2'-((1E,1'E)-(1,2-phenylenebis(azanylylidene))bis(methanylylidene))bis(4-fluorophenol) (L1F), and 2,2'-((1E,1'E)-(1,2-phenylenebis(azanylylidene))bis-(methanylylidene))bis(4-methylphenol) (L1M) with nickel(II) acetate tetrahydrate to form NiL1H, NiL1F and NiL1M. The chemical structures were elucidated through physicochemical and spectral techniques namely elemental analysis, melting point, FTIR, 1H and 13C NMR, magnetic susceptibility and molar conductivity. All nickel(II) complexes were tested as catalysts in homogenous Sonogashira reaction between iodobenzene and phenylacetylene in DMSO for 12 hours at 140 oC. NiLF, a new nickel(II) complex, converted the highest percentage of iodobenzene (91%) while NiLH and NiLC converted 78% and 83% of iodobenzene, respectively.Â